The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.2165/00019053-200321090-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Medical Costs of Atherothrombotic Disease in European Countries

Abstract: There are differences in the overall costs and cost breakdown in the clinical management patterns of MI and IS in Europe. These differences seem to arise as a result of local treatment pattern specificities as well as the availability of specific and well-adapted structures for patients' rehabilitation. Further studies are necessary to fully explain these differences. The assessment of the total medical costs of managing an atherothrombotic patient over a 2-year period (MI, IS, established PAD) has to take int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 11 publications
2
33
0
4
Order By: Relevance
“…First, we estimate the average cost of hospital treatment for ACS to be about 12.101 Euro. These results appear to be in line with the findings of other investigations [6,7,20,21]. Levy et al described an amount of 12.393 Euro for the cost of treating a myocardial infarction in the Swiss population.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…First, we estimate the average cost of hospital treatment for ACS to be about 12.101 Euro. These results appear to be in line with the findings of other investigations [6,7,20,21]. Levy et al described an amount of 12.393 Euro for the cost of treating a myocardial infarction in the Swiss population.…”
Section: Discussionsupporting
confidence: 91%
“…Levy et al described an amount of 12.393 Euro for the cost of treating a myocardial infarction in the Swiss population. Their estimation, however, was based on a smaller sample size [7]. Matsui and colleagues found the same duration of stay in the intensive care unit (two days) in the late nineties, but a longer hospitalization on the general ward in Switzerland (12 days).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies (12,(35)(36)(37)(38)(39)(40)(41)(42) reported costs associated with CAD overall or specifically for myocardial infarction (MI), acute coronary syndrome (ACS) and angina. These studies are summarized in Table 5 and are discussed in more detail below.…”
Section: Cadmentioning
confidence: 99%
“…Acute costs of MI and one-year follow-up also represented the largest proportion of the costs of MI in Europe when a decision tree model was used to estimate the two-year cost of MI in eight European countries (38). ACS: In a retrospective analysis of a managed care database (36), hospitalization and drug costs represented 72% and 7% of the twoyear medical costs associated with new-onset ACS patients, respectively.…”
Section: Cadmentioning
confidence: 99%